2021
DOI: 10.1021/acs.biochem.1c00399
|View full text |Cite
|
Sign up to set email alerts
|

Transport Dynamics of MtrD: An RND Multidrug Efflux Pump from Neisseria gonorrhoeae

Abstract: The MtrCDE system confers multidrug resistance to Neisseria gonorrhoeae, the causative agent of gonorrhea. Using free and directed molecular dynamics (MD) simulations, we analyzed the interactions between MtrD and azithromycin, a transport substrate of MtrD, and a last-resort clinical treatment for multidrug-resistant gonorrhea. We then simulated the interactions between MtrD and streptomycin, an apparent nonsubstrate of MtrD. Using known conformations of MtrD homologues, we simulated a potential dynamic trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In the same year, Ammerman et al [ 105 ] studied substrate (azithromycin) and non-substrate (streptomycin) interactions and dynamics with the same RND transporter using free and targeted MD simulations. The authors determined the spontaneous diffusion of azithromycin through CH2 and found that it takes an unexpected pathway along PN1, bypassing the DP altogether.…”
Section: Mechanism Of Substrate Transportmentioning
confidence: 99%
“…In the same year, Ammerman et al [ 105 ] studied substrate (azithromycin) and non-substrate (streptomycin) interactions and dynamics with the same RND transporter using free and targeted MD simulations. The authors determined the spontaneous diffusion of azithromycin through CH2 and found that it takes an unexpected pathway along PN1, bypassing the DP altogether.…”
Section: Mechanism Of Substrate Transportmentioning
confidence: 99%
“…These peptides likely enter gonococci and bind to this efflux pump and, as a consequence, decrease efflux activity. Advances in determining the structure of MtrD complexed with antibiotics in the proximal or deep binding pockets could facilitate structure-based approaches to develop specific, safe inhibitors that act at designated sites within this transporter [72–75]. With specific regard to gene regulation, the results of Chen et al .…”
Section: Exploiting Knowledge Of Regulation For Therapeutic Purposesmentioning
confidence: 99%